Bank Syariah Indonesia: Its Impact and Prospects on The Economy in Indonesia - Deha, Damai; Fasa, Muhammad Iqbal; Suharto, Suharto (Journal of Islamic Economics and Social Science (JIESS), 2023)
On February 1, 2020, the Islamic banking sector under the auspices of BUMN inaugurated a merger of Islamic banks including BRI Syariah, BNI Syariah, and Bank Syariah Mandiri merging to become Bank Syariah Indonesia. The merger of these three banks will have complete competence, because each merged bank has its own advantages. Merger can be defined as a business union and / or joint supervision, the merger of two or more companies under one ownership, and the takeover of all assets and liabilities owned by a company to be merged with a company that takes over or a new company. The research method used is descriptive qualitative research. It can be seen that the results of the merger of 3 Sharia banks have had an impact on the economy in Indonesia, including printing millennial entrepreneurs through business incubator scholarships, collaborating with the Ministry of Tourism and Creative Economy to target MSME financing in the tourism sector and creative economy, developing the Sharia economy by collaborating with research institutes and universities, and some. The prospect of establishing Bank Syariah Indonesia can provide access to Islamic financial solutions in Indonesia, become a large bank that provides the best value for shareholders and becomes the company of choice and pride for Indonesia's best talents.